PENGARUH MOTIF PRIBADI DALAM PENGGUNAAN MEDIA INTERNAL TERHADAP PEMENUHAN KEBUTUHAN INFORMASI KARYAWAN PT KERETA API INDONESIA (PERSERO) KANTOR PUSAT BANDUNG - Azmita Rizkiwantie; Roro Retno Woelan; Ayub Ilfandy Imran (Dialektika, 2016)
PT Kereta Api Indonesia (Persero) is a State Owned Enterprises (SOE) engaged in public transport. Until now, the use of the print media internal is still maintained by PT KAI as an internal communication media to tell the information about the company. The print media internal is called ‘Tabloid Kontak’. Tabloid Kontak is an acronym for communication between employees, which is estabilished since 1973 . The purpose of this research is to know the influence of personal motives on the usage of internal media towards the employees’ information needs of PT KAI with the use of internal media tabloid Kontak as an intervening variable. This research used some relevant theories such as communications, uses and gratification, public relations and information needs. The variables in this study are related and included the model of Uses and Gratification. Method of this research used is quantitative method and inferential analysis with associative approach. Respondents of the study involved 173 employees of head Office PT KAI, with the technique sampling used is propability sampling. Analysis data in this research was using path analysis. The results of this research indicate that personal motives affect the information needs of yhe employees (58,36%), personal motives affect the use of internal media tabloid Kontak (10,62%), the use of internal media tablod Kontak affect the information needs of the employees (28,11%) and personal motives affect the information needs of the employees through the use of internal media tabloid Kontak as an intervening variable (68,9%) and indirectly (17,3%).